The long pentraxin 3: the invisible loom weaving the warp and weft of tumor destiny - Liu, Tianyi; Li, Manyu; Cheng, Yuxi; Zou, Jialin; Liu, Fengying; Dong, Jie; Qiu, Cheng; Peng, Xuenan; Kong, Deyang; Li, Zhifan; Wang, Xinyu; Li, Lanyu (Frontiers in Immunology, 2025)
Pentraxins, which constitute a family of evolutionarily conserved pattern recognition molecules, are categorized into short and long branches. The long pentraxin 3 (PTX3) is a key member of the long pentraxin subfamily, while the C-reactive protein and serum amyloid P represent the short pentraxins. All pentraxins share a highly conserved C-terminal motif, an 8-amino acid sequence known as the pentraxin signature. PTX3 can be produced by a wide range of cell types, including immune cells such as dendritic cells, monocytes, and macrophages, as well as various non-immune cells, underscoring its pleiotropic roles in multiple pathophysiological processes. These include inflammation, infection, tissue repair, female fertility, and cancer. Although PTX3 engages commonly recognized signaling pathways, such as TNF-α, NF-κB, FGF, and PI3K/AKT, it can exert paradoxical effects in different cellular contexts, either promoting or inhibiting the proliferation, migration, invasion, and metastasis of cancer cells. This review provides a comprehensive overview of the multifaceted roles of PTX3 in various cancers, while also summarizing its functions in other physiological or pathological contexts. Furthermore, we critically examine the challenges and translational opportunities of PTX3, aiming to inform future research directions and therapeutic strategies for cancer management.